Evaluation Of Bio-Medical Waste Management Practices in A Government Medical College and Hospital - Srivastav Shalini; Mahajan Harsh; Mathur B P (Medsci Publications, 2012)
Background: Biomedical waste (BMW) collection and proper disposal has become a significant concern for both the medical and the general community as improper management poses risks to the health care workers, waste handlers, patients, community in general and largely the environment. Objectives: (i) Assessment of current Bio-medical waste management practices including collection, segregation, transportation, storage, treatment and disposal technologies in tertiary health care center. (ii) Assessment of health and safety practices for the health care personnel involved in Bio-Medical Waste Management. Materials and Methods: Waste management practices in the Government Hospital was studied during March 2009 - May 2009.The information / data regarding Bio-Medical Waste Management practices and safety was collected by way of semi- structured interview. Results: M.L.B Medical College generates 0.52Kgs waste per bed per day and maximum waste is generated in wards. The institute has got separate color coded bins in wards for collection of waste but segregation practices needs to be more refined. The safety measures taken by health care workers was not satisfactory, it was basically due to un-awareness of health hazards which may occur because of improper waste management practices. Conclusion: Thus it is concluded that there should be strict implementation of a waste management policy set up in the institute; training and motivation must be given paramount importance to meet the current needs and standards of bio-medical waste management.